Gasification of Malaysian agricultural and industrial biomass in CO2: a physicochemical characterization and thermogravimetric-based ranking approach - Ng, Zi Wei; Salema, Arshad Adam; Ibrahim, Izzudin; Lahuri, Hazratul Mumtaz; Chan, Yi Herng (Elsevier, 2025)
Currently, industries capture and store carbon dioxide (CO2), but they are seeking a long-term solution to convert the captured CO2 into value-added products. The main aim of this study is to rank the Malaysian agricultural and industrial biomasses: empty fruit bunches (EFB), palm kernel shell (PKS), sawdust (SD), rice husk (RH), and coconut shell (CS) based on physicochemical properties, kinetic, thermodynamic parameters, and their interaction with CO2 (gasifying agent), utilizing thermogravimetric analysis (TGA). Gasification proceeded via a two-stage thermal degradation process: pyrolysis (below 380 °C - I) and char gasification (beyond 380 °C - II). Kinetic analysis revealed a catalyst-induced reduction in activation energy during Stage II. Thermodynamic analysis showed positive enthalpy change (ΔH) exhibited endothermic reaction requirements, while positive Gibbs free energy change (ΔG) indicated a non-spontaneous process. EFB emerged as the top-ranked biomass (EFB > PKS > CS > SD > RH) based on integrated characterization, kinetic, and thermodynamic outcomes. The application of dolomite and olivine catalysts significantly enhanced gasification kinetics, particularly for EFB and RH, by reducing ΔH. The biomass ranking framework will benefit researchers and industries to prioritize biomass feedstock based on their performance, paving the way for the practical implementation in CO2 gasification.